Penambahan alternator pada mesin ketinting untuk melayani kebutuhan daya lampu nelayan tradisional di malam hari - Suartika, I.M.; Okariawan, I.D.K.; Saputra, W. (Universitas Mataram, 2022)
In this study the ketinting machine was modified by adding an alternator. By adding alternators aimed at supplying the power needs of lights for lighting when fishermen operate at night. The ketinting machine is dikopel with pully on its long shaft, and the pully is connected with the alternator using a V-belt, so that when the ketinting machine is turned on the alternator will rotate supplying the light power and charging the battery. When you do not turn on the lights, the alternator will charge the battery only. The method used in this study is an experiment in the laboratory to determine the effect of engine modifications on battery charging time and fuel consumption. Modifications resulted in a change in engine dimensions from 353 x 374 x 346 mm to 346 x 514 x 413.23 mm. The time it takes to charge the battery is affected by the engine rotation. The larger the engine revs the smaller the time it takes to fill the battery to the full. At 1500 rpm the charging time is 16 Hours 12 minutes, the 2000 rpm spin is 11 Hours 2 minutes, and the 2500 rpm spin is 7 Hours 15 minutes. Fuel consumption increased by 80-90 percent in liters/hour from before it was modified with after it was modified. Technically this modification of ketinting engines can help fishermen's operations at night but its feasibility economically needs further research